Commercializing Quantum Keys. - Moore, S.K (IEEE spectrum)
Several firms, including ID Quantique, MagiQ, and SmartQuantum, are working on turning the esoteric quantum properties of light into money. These firms are trying to sell a way of distributing a cryptographic key that is theoretically theft-proof because it relies on the quirky quantum physics of photons. Such a quantum key distribution system could allow entities with secrets to encode and decode their data for transmission over optical fiber. Quantum key distribution lets two computers generate a key between them by taking advantage of a quantum property of photon. A quantum key can be generated by transmitting a series of bits encoded using one or a few photons per bit and two types of polarization filters